RIFM fragrance ingredient safety assessment, acetic acid, anhydride, reaction products with 1, 5, 10-trimethyl-1, 5, 9-cyclododecatriene, CAS registry number 144020-22-4. (December 2019) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Highlights: Acetic acid, anhydride, reaction products with 1, 5, 10-trimethyl-1, 5, 9-cyclododecatriene; safety assessment, RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.